2011
DOI: 10.1159/000324210
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Sensorineural Hearing Loss: Subclinical Viral and Toxoplasmosis Infections as Aetiology and How They Alter the Clinical Course

Abstract: Aim: To explore in a prospective study the evidence of certain viral and toxoplasmosis infections in sudden sensorineural hearing loss (SSHL). Methods: 84 consecutive patients with SSHL meeting certain criteria. All patients were assessed for specific IgM antibodies against cytomegalovirus, herpes simplex virus, toxoplasma and Epstein-Barr virus. All were treated with intravenous steroids and assigned to two groups: 76 IgM negative (NV group) and 8 IgM positive (no history of acute infection – V group). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“…Diagnoses of certain types of chronic infection have been significantly associated with subsequent SSNHL. 15,16 However, the mechanism underlying the association between COM and subsequent SSNHL remains unclear. The risk factors for chronic sensorineural hearing loss are middle ear infections, which are also important in the development and progression of labyrinthitis.…”
Section: Underlying Mechanism Of Ssnhl In Com-positive Patientsmentioning
confidence: 99%
“…Diagnoses of certain types of chronic infection have been significantly associated with subsequent SSNHL. 15,16 However, the mechanism underlying the association between COM and subsequent SSNHL remains unclear. The risk factors for chronic sensorineural hearing loss are middle ear infections, which are also important in the development and progression of labyrinthitis.…”
Section: Underlying Mechanism Of Ssnhl In Com-positive Patientsmentioning
confidence: 99%
“…As a transcription factor, GRHL2 is important in embryonic development and otic epithelial tissue differentiation by promoting apical junction maturation (14,26,27). GRHL2 could also be involved in apical barrier formation and activate adult antimicrobial defense, which may be associated with SSHL observed in viral infections (28,29). GRHL2 could Table IV.…”
Section: Discussionmentioning
confidence: 99%
“…GRHL2 is important in embryonic development and otic epithelial tissue differentiation by promoting apical junction maturation. Research has shown that GRHL2 plays an important role in apical barrier formation and adult antimicrobial defense, which may be associated with SSNHL observed in viral infections [Kikidis et al, 2011]. A great number of previous studies have reported that genetic polymorphisms in GRHL2 are the cause of autosomal dominant sensorineural hearing loss and are correlated with the development of age-related hearing impairment [Fransen et al, 2008;Konings et al, 2009;Li et al, 2013].…”
Section: Doi: 101159/000497032mentioning
confidence: 99%